2018
DOI: 10.1002/cncr.31251
|View full text |Cite
|
Sign up to set email alerts
|

Imaging‐based biomarkers: Changes in the tumor interface of pancreatic ductal adenocarcinoma on computed tomography scans indicate response to cytotoxic therapy

Abstract: BACKGROUNDThe assessment of pancreatic ductal adenocarcinoma (PDAC) response to therapy remains challenging. The objective of this study was to investigate whether changes in the tumor/parenchyma interface are associated with response.METHODSComputed tomography (CT) scans before and after therapy were reviewed in 4 cohorts: cohort 1 (99 patients with stage I/II PDAC who received neoadjuvant chemoradiation and surgery); cohort 2 (86 patients with stage IV PDAC who received chemotherapy), cohort 3 (94 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
(31 reference statements)
1
28
0
Order By: Relevance
“…Toward identification of the primary tumor, Fishman and colleagues have described a radiomics-based machine learning algorithm to differentiate PDAC from benign situations (i.e., normal pancreas and pancreatitis) with high specificity and sensitivity 112 . Other applications of radiomics and quantitative imaging approaches have shown that the enhancement and morphology of the primary tumors have biological underpinnings and clinical relevance [113][114][115] , suggesting that quantitative imaging and further application of AI to these imaging features can provide non-invasive insight into the disease. This insight may have relevance to early detection through better stratification and personalized approaches to screening in high-risk individuals.…”
Section: Deep Learning Methodologies Applied To Abdominal Imagingmentioning
confidence: 99%
“…Toward identification of the primary tumor, Fishman and colleagues have described a radiomics-based machine learning algorithm to differentiate PDAC from benign situations (i.e., normal pancreas and pancreatitis) with high specificity and sensitivity 112 . Other applications of radiomics and quantitative imaging approaches have shown that the enhancement and morphology of the primary tumors have biological underpinnings and clinical relevance [113][114][115] , suggesting that quantitative imaging and further application of AI to these imaging features can provide non-invasive insight into the disease. This insight may have relevance to early detection through better stratification and personalized approaches to screening in high-risk individuals.…”
Section: Deep Learning Methodologies Applied To Abdominal Imagingmentioning
confidence: 99%
“…At our institution, Amer et al recently evaluated 4 cohorts of patients and showed that in each, the change in the radiographic interface between tumor and adjacent pancreatic parenchyma that often occurred in association with (chemo)radiation was associated with outcome. Moreover, in one of the cohorts, patients who met criteria for a radiomic response had a greater likelihood of achieving a pMR or pCR (21 vs. 0%, P = 0.01) (54). Our group has also identified an imaging biomarker that can be assessed using routine computer tomographic images and may be used to stratify patient's tumors into distinctive biophysical subtypes (55).…”
Section: Future Perspectives: Bio-imaging and Bio-markersmentioning
confidence: 90%
“…Another limitation is that there is currently no biomarker to determine which patients are ideal for consolidation with radiation and who might benefit from EGLN inhibitors. For the former, there is continuing work on histologic biomarkers such as SMAD4 (38), circulating tumor DNA (39), and radiomic (40,41) approaches. For the latter issue, there is no clinically accepted biomarker for hypoxia.…”
Section: Discussionmentioning
confidence: 99%